Mendorong Transparansi dan Akuntabilitas Dana Kampanye pada Penyelenggaraan Pilkada Serentak Tahun 2018 (Universitas Medan Area, 2018)
So important is the role of the campaign to be able to attract and convince voters, where the more massive and intensified campaigns are carried out, the greater the campaign funds needed. With large funding, election participants have a greater opportunity to convince voters. When the campaign requires large funds, what will be a problem is the legitimacy of the sources of funds collected, for which there is a need for rules that can overcome the problem. For this reason, the General Election Commission (KPU) has made legal regulations to ensure that campaign funds used by election participants come from legitimate sources. Campaign funding arrangements start with the creation of special accounts for campaign funds, arrangement of funding sources and restrictions on the number of donations. Campaign funds must be submitted to the Election Commission as a form of accountability through campaign finance reports. This campaign fund report was then audited by the Public Accountant Office (KAP) which was formally appointed by the KPU to ensure that the reports submitted fulfilled the compliance aspects or not. The administrative sanctions are given for each violation related to the use and reporting of campaign funds. With a series of rules above, it is expected to be able to encourage transparency and accountability of election fund campaign campaign reports.